Polymerization Styrene dengan Solven Toluena - Sri Wahyu Murni; Wasir Nuri; Indriana Lestari; Ani Saraswati (Eksergi, 2009)
Polystyrene is the result of free radical-addition polymerization of styrene monomer with the initiator benzoyl peroxide. This research aims to study the effect of variable temperature and ratio of toluene-styrene (T / S) against the conversion and reaction kinetics of polymerization of styrene with toluene solvent and initiator benzoyl peroxide. This research was conducted in two stages, ie preliminary experiments with test FTIR (Fourier Transform Infra-Red) to prove that the manufacture of polystyrene was successful. Manufacture of polystyrene begins with purifying styrene monomer, and then enter a toluene-styrene (5:1 volume ratio, 5:2, 5:3, 5:4) and 0.2 gram of benzoyl peroxide into a three-neck flask and heated to the desired temperature (60, 70, 80, 90 and 100)oC. Samples were taken every 15 minutes. Each sample is added 0.01 grams of hydroquinone in 10 ml of ethanol and shaken gently to precipitate the polystyrene, then wet samples were weighed, put in oven at 200oC for 1.5 hours. Dried sample was cooled in eksikator then weighed to determine the weight of polystyrene formed. From the experimental results at optimum condition of reaction time of 120 minutes, the temperature of 100oC and toluene-styrene ratio of 5:4, obtained by conversion of 58.75%. The global rate reaction according to equation k' = 5963 exp (-8901 / T).